Gerenciamento de incertezas nas tarefas de interpretação simultânea de Libras para o português - Sousa, Marília Santos de (2024)
Currently, the translation and interpretation of sign language have become significantly prominent, fostering the consolidation of a specific field of research known as Sign Language Translation and Interpretation Studies, hereafter referred to as ETILS. In this context, the goal of this research is to investigate how Brazilian Sign Language (Libras) interpreters manage uncertainties in simultaneous interpretation tasks involving languages of different modalities, such as the vocal-auditory (spoken language - Portuguese) and the visual-manual (signed language - Libras). The specific objectives of this study are to investigate which uncertainties arise during simultaneous interpretation tasks and to determine the most commonly applied strategies for managing these uncertainties. However, since this research falls under Interpretation Studies, even as a subfield of Translation Studies, it will reference authors more directly associated with Interpretation Studies, henceforth referred to as IS, such as Gile (1995, 2000, 2011) and Pöchhacker (2004, 2005). In addition to the theoretical contributions from Sign Language Studies by Albres (2014, 2015), Quadros (2005, 2009), Rodrigues (2016, 2018), this study proposes an approach that integrates theoretical perspectives from Cognitive Studies, with scholars like Angelone (2010) and Flavell (1979), among others. The methodology adopted is qualitative, with a descriptive exploratory nature, relying on the analysis of a corpus of interpretation, complemented by questionnaires administered before and after interpretative sessions. For data analysis, the principles set by Angelone (2010) will be followed, assessing the emergence of uncertainties in the three main cognitive processes he identifies: a) understanding of the source language text, b) transfer of meaning, and c) production of text in the target language. We recognize that all interpretative processes require cognitive effort, making it essential for the Libras interpreter to engage in reflective practice in these types of interpretative demands and, consequently, to strengthen their decision-making capacity when performing interpretations into Portuguese.